Lexical interference: comparison of Uzbek and English languages - Boltaboyev Farxodjon Shavkat o'g'li (Genius Journals, 2023)
The current state of scientific development of topical problems of linguistics, the tasks of lexicology, the prospects for the general development of the theory of meaning and evaluation necessitate the search for linguistic innovations, a new look at previous problems and involve many questions that have not been studied comparison in the orbit of scientific research in linguistics.
Keywords: Languages; various signs; Uzbek and English